Implication of Rho-kinase and soluble guanylyl cyclase enzymes in prostate smooth muscle dysfunction in middle-aged rats - Calmasini, Fabiano B.; Silva, Fabio H.; Alexandre, Eduardo C.; Rodrigues, Renata L.; Barbosa, Ana Paula L.; Ferrucci, Danilo L.; Carvalho, Hernandes F.; Anhê, Gabriel F.; Pupo, Andre S. [UNESP]; Antunes, Edson (Wiley, 2017)
Aims: Aging is highly associated with benign prostate hyperplasia (BPH). We investigated here the alterations of the contractile and relaxant machinery in prostates of middle-aged rats, focusing on the Rho-kinase, nitric oxide (NO)-soluble guanylyl cyclase (sGC), α1- and β-adrenoceptor pathways. Methods: Male Wistar young (3.5-month old) and middle-aged rats (10-month old) were used. Quantitative image analysis of prostates and functional assays evaluating the prostate contractions and relaxations were employed. Measurement of [3H]-noradrenaline efflux, western blotting for α1 and β1 sGC subunits, and cyclic nucleotide levels were carried out. Results: Prostates of middle-aged rats showed significant increases in lumen and smooth muscle cells, but no alterations in the relative prostate weight were observed. In vivo, noradrenaline (10−7–10−4 g/kg) produced greater prostatic contractions in middle-aged compared with control rats. Likewise, the in vitro contractions to phenylephrine (1 nM–100 μM) and α,β-methylene ATP (1–10 μM) were greater in middle-aged rats. Electrical-field stimulation (EFS, 1–32 Hz) promoted higher [3H]-noradrenaline efflux and prostate contractions in middle-aged rats. Reduced expressions of α1 and β1 sGC subunits and diminished NO-mediated prostate relaxations in middle-age were observed. Isoproterenol-induced relaxations and cAMP levels were reduced in prostates of middle-aged rats. The Rho-kinase inhibitor fasudil (50 mg/kg, 2 weeks) normalized the prostate hypercontractility in middle-age rats. Conclusions: Prostate hypercontractility in middle-aging is associated with increased release of noradrenaline and Rho-kinase pathway, as well as with impairments of NO-sGC and β-adrenoceptor pathways. Middle-aged rats are suitable to explore the enhanced prostatic tone in the absence of prostate overgrowth. Neurourol. Urodynam. 36:589–596, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: aging; cyclic AMP; protein kinase C; stereology; β-adrenoceptors